Referential and Vehicular Languages in the Process of Migrant Integration - Angulo, Mónica Ibáñez (Border Crossing, 2017)
In this article I examined the strategies developed by Bulgarian immigrants living in Spain in order to promote the learning of Bulgarian language and culture among their children. Starting from the incorporated cultural capital brought by immigrants in the form of habitus (Bulgarian language and culture), I analyse how this devaluated cultural capital in the migratory context is effectively reconverted in other forms of cultural capital (objectified and institutionalized) through the development of non-formal and formal courses on Bulgarian language and culture. In this analysis I show the articulation between, on the one hand, the contexts where these informal, non-formal and formal courses take place and, on the other hand, the reconversion of different forms of social and cultural capital: the initial bonding social capital between family members and close group of compatriots is effectively reconverted into bridging and linking social capital as the organization of these courses requires and contributes to the diversification of social networks. The analysis has also a gender dimension given that in most cases, and certainly in the case of Burgos, women are the main social actors and makers of these strategies. The main objective of the article is to show the relevance of social interaction and social networks in the development of reconversion strategies of different forms of social and cultural capital. In addition, the article also expects to raise more awareness towards the relevance of mother-tongue learning in the migratory context.